1991
DOI: 10.1093/oxfordjournals.annonc.a057979
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of second over first generation chemotherapy in a randomized trial for stage III-IV intermediate and high-grade Non-Hodgkin's Lymphoma (NHL): The 1980–1985 EORTC trial

Abstract: A first-generation CHOP-like cyclic combination chemotherapy (CT) regimen using cyclophosphamide 600 mg/m2 IV d1, hydroxorubicin (doxorubicin) 50 mg/m2 IV d1, VM26 60 mg/m2 IV d1, and prednisone 40 mg/m2 PO d1-5 (CHVmP) was compared to a second-generation combination wherein vincristine 1.4 mg/m2 IV and bleomycin 6 mg/m2 IM/IV were added at mid-interval (d15) to the former drugs (CHVmP + VB) in the treatment of intermediate- and high-grade malignant NHL. From April 1980 to January 1986, 141 eligible patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…[32][33][34][35] No cumulative total dose doxorubicincomplication relation could be estimated, because dose information of salvage treatment was often lacking.…”
Section: Treatmentmentioning
confidence: 99%
“…[32][33][34][35] No cumulative total dose doxorubicincomplication relation could be estimated, because dose information of salvage treatment was often lacking.…”
Section: Treatmentmentioning
confidence: 99%
“…The previous conventional chemotherapy regimens have attained complete remission in about 50% of patients1-3). The best available regimen, the CHOP combination chemotherapy, has been widely used, but the prognosis of the partial responders to CHOP therapy is very poor with only 0~25% of patients becoming long-term survivors17).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of non-Hodgkin's lymphoma (NHL) has been considerably improved for attaining complete remission and long-term survival in approximately 50% of patients1-3). However, the prognosis of the patients who are refractory to treatment or who relapse with NHLs is dismal at best4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…However, a dose-intensive third generation regimen Pro-MACE-CytaBOM has recently in a randomized study been shown to improve survival when compared with a second generation regimen ProMACE-MOPP ( lo), and another randomized study showed that the addition of bleomycin and vincristine at mid-interval (d. 15) of a CHOP-like first generation regimen CHVmP (cyclophosphamide, doxorubicin, VM-26, and prednisone) resulted in a better outcome (11). A feasible and well-tolerated way to combine active drugs with low myelotoxicity, such as bleomycin, vincristine and methotrexate, with more myelotoxic drugs may be an important reason for these results.…”
Section: Discussionmentioning
confidence: 99%